2010
DOI: 10.1161/circheartfailure.109.854026
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Clinical Significance of Late Gadolinium Enhancement by Contrast-Enhanced Magnetic Resonance Imaging in Patients With Hypertrophic Cardiomyopathy

Abstract: Background-Myocardial late gadolinium enhancement (LGE) on contrast-enhanced magnetic resonance imaging (CE-MRI) of patients with hypertrophic cardiomyopathy (HCM) has been suggested to represent intramyocardial fibrosis and, as such, an adverse prognostic risk factor. We evaluated the characteristics of LGE on CE-MRI and explored whether LGE among patients with HCM was associated with genetic testing, severe symptoms, ventricular arrhythmias, or sudden cardiac death (SCD LGE positive (event rate of 0.94%/y, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
229
4
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(264 citation statements)
references
References 39 publications
16
229
4
11
Order By: Relevance
“…Amounts of myocardial fibrosis in human HCM hearts correlate with the degree of hypertrophy (37), diminished ventricular performance (38), diastolic dysfunction (16), and energy demands (39) -factors that contribute to heart failure and may increase arrhythmic risk (40,41). As such, the benefit from inhibiting fibrosis in HCM could be substantial.…”
Section: Discussionmentioning
confidence: 99%
“…Amounts of myocardial fibrosis in human HCM hearts correlate with the degree of hypertrophy (37), diminished ventricular performance (38), diastolic dysfunction (16), and energy demands (39) -factors that contribute to heart failure and may increase arrhythmic risk (40,41). As such, the benefit from inhibiting fibrosis in HCM could be substantial.…”
Section: Discussionmentioning
confidence: 99%
“…replacement, interstitial and plexiform type with overlapping patterns which alone cannot be differentiated from scarring seen in other types of cardiomyopathies seen as late gadolinium enhancements(LGE's).The histological correlate of LGE in HCM seems to be increased myocardial collagen rather than myocardial disarray which is also observed on histological specimens and is postulatedto reflect microvascular ischemia and microscopic replacement fibrosis due to small intramural coronary arteriole dysplasia. 5,6 Another alternative hypothesis for LGE in HCM suggested that the causative sarcomeric gene mutations might lead to a phenotypic expression of increased myocardial connective tissue deposition, 7 Hence there is a need to detect myocardial fibrosis and quantify the excessive collagen deposition in the Myocardium. Detection of myocardial fibrosis by LGE is variable in different HCM cohorts and is between 40-80%.Traditionally found patterns are patchy mid myocardial LGE, patchy LGE at RV insertion points and diffuse confluent trans mural pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The association with the obstruction was not found in a study in which the prevalence of obstructive forms was similar between those with and without DE 76 . Longitudinal analyses showed relation between DE, sudden death and increased mortality, but it is still not proved [76][77][78] . Further investigations are necessary for the DE to be recognized as an independent prognosis predictor and a factor predisposing to sudden death 2 .…”
Section: Magnetic Resonance Imagingmentioning
confidence: 92%
“…MRI with gadolinium detects and quantifies fibrosis areas with delayed enhancement (DE) of focal or diffuse character in 60-80% of patients with HCM, representing 0-40% of the LV myocardial mass [74][75][76][77][78] (Figure 4). The DE is associated with the record of nonsustained ventricular tachycardia in Holter in multivariate analyses 75,78 , as well as the left ventricular reshaping and evolution of terminal dilated forms 74 .…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation